Social Computing of the Social Well-being of Refugees and Internally Displaced Persons in Ukraine Using Data Mining Methods - Biryukova, Marina; Kyrychenko, Iryna; Shanidze, Nadiia; Shanidze, Oleksandr (My University, 2023)
The article is devoted to the study of the possibility of using intelligent computer systems using the analysis of knowledge bases on large arrays of sociological information. The state of social well-being of refugees and forcibly displaced persons during the military aggression against Ukraine in 2022 (N 1170) was studied using factor analysis, the method of classifications, methods of multidimensional scaling and two-dimensional distribution of data. The possibilities of computer processing of sociological information have been determined, which contributes to the emergence of approaches to obtaining new scientific knowledge, among which intelligent data analysis (IAD), based on the use of computer analysis methods and artificial intelligence in the search for latent knowledge hidden in arrays of source information.
Keywords: social computing; social well-being; array of sociological information; factor analysis; refugees and forcibly displaced persons